Social roles of the elderly in six municipalities in Cavite their determinants - Rafanan, Reuben R. 1952- (1995)
The general objective of this research was to study the relationship of psychosocial, socio-demographic, and health factors and the performance of the social roles of the elderly in six municipalities in Cavite Province, Republic of the Philippines. The six study municipalities were Alfonso, General Aguinaldo, Magallanes, Maragondon, Mendez, and Ternate, all serving as laboratory municipalities of the University of the Philippines, College of Public Health (UP CPH). The dependent variable, social roles, was categorized into the following: (1) kinship/family and ethnic roles; (2) Economic roles; (3) Social and community participation roles; (4) Religious roles; (5) Political roles; and (6) Recreational roles. Three groups of respondents took part in the study. The first group are the elderly respondents (60 years old and above) who numbered 362 randomly selected from the six study municipalities. The respondents were the main group of subjects and the responses of the two other group of respondents were used as bases for comparison. The second group of respondents were the responsible persons, a group o care-givers who were named by the elderly respondents as individuals who give them care and help when these were needed. There were 348 responsible-person respondents. The third group of respondents are medical doctors--the six Municipal Health Officers of the study municipalities. Each elderly respondents was given a physical check-up by the medical doctors in order to establish a more objective picture of the health status of the elderly subjects, as opposed or compared to the subjective assessments of the elderly subjects of their health status. Treating the psychosocial factors as a group of determinants of the performance of the social roles by the elderly subjects, it was found out that it was only the factor Social Expectations (among the four indicators of psychosocial factors) that had a significant influence over the performance of social roles by the elderly subjects. This factor explained for 75.053 percent of the variations in the performance of the elderly's social roles. There were eight indicators of the independent variable Socio-Demographic Factors. When the social roles underwent multiple regression statistical treatment, three factors emerged as having significant influence over the performance of the elderly's social roles. These were: (1) the perceived social roles of the elderly by members of the elderly's household; (2) the socio-economic status of the elderly; and (3) the family structure/living arrangements of the elderly. These three factors explained for 76.090 percent of the variances in the performance of the social roles of the elderly. Of these three, the perceived social roles of the elderly by the members of the elderly's household explained for 75.013 percent of the variances in the performance of the elderly's social roles. The health factor that showed a significant influence over the performance of the social roles of the elderly is the general health evaluation by the elderly of his(er) health status. This explained for 10.629 percent in the variances in the performance of the social roles of the elderly. The last factor that came out when the three groups of determinants were treated as a single category of determinants was the accessibility and availability of facilities for the elderly's social interactions and health responsibilities. Basing on the results of the study, the following profile exists for the elderly who perform their social roles. 1. They have social roles they perceive they could still perform that are congruent with what others expect them to perform. 2. They have higher socio-economic status; 3. They perceive themselves to be generally in good health; 4. They have closely-knit family ties and comfortable living arrangements; and 5. They have access to facilities carrying out their social interactions and health responsibilities.